Analysis of Different Types of Tea Leaves by X-Ray Flourescence Technique - Mandi, K.H.; Al-Kubaisy, R.K.; Al-Mousawi, M.A.; Daoud, S. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Samples of tea leaves (Green tea, Gugarate tea and Black tea used commonly in Iraq) are dried, grinded, pressed and submitted for the elemental analysis by x-ray fluorescence technique (XRF). The concentrations of major, minor and trace elements are determined. The major elements were Na, Mg, Al, K, Si, Ca, Mn, Fe, S and P. Of these elements, Ca, concentration in Gugarate tea leaves is three times, it's level in the other types of tea. Titanium, Cl, Rb and Sr are found as minor elements, while other elements such as Cu, Zn, V, Cr, Co, ...etc are found as trace elements. Of these trace elements considerable concentration values are found for some toxic elements Hg, Cd, Pb and As. Green tea contains 1.1 ppm Hg and 4.4 ppm Pb. Gugarate tea contains 0.8 ppm Hg, 5.8 ppm Pb and 6 ppm As. Black tea contains 2.4 ppm Pb. Chromium, Zinc and Copper found in considerable concentrations with respect to the other trace elements in all analysed samples.